Encapsulated Cadmium Sulfide in Silicon Dioxide Porous Shells for Enhanced Photocatalytic Sustainability and Commendable Protection of Organic Carriers. Issue 8 (5th March 2019) - Zhao, Jian; Tian, Shengnan; Shi, Haiting; Quan, Quan; Xiao, Changfa
Abstract: The purpose of this study is to provide a solution to two troublesome problems on photocorrosion of cadmium sulfide (CdS) and photocatalysis damage to organic carrier. An encapsulation system of CdS in silicon dioxide (SiO2 ) porous shell can be constructed by following strategies: polyporrole (PPy) layer is deposited on the surface of CdS nanoparticles via chemical redox polymerization; then the resulting PPy@CdS is covered by metasilicic acid (H2 SiO3 ) with polyethylene glycol by sol–gel process, which originates from hydrolysis of tetraethyl orthosilicate; after removing PPy interlayers by calcination, CdS@void@SiO2 yolk–porous‐shell nanospheres (YSNs) are fabricated. As expected, YSN nanoarchitecture is verified by transmission electron microscopy (TEM) and Brunauer–Emmett–Teller (BET) analysis. The tailored void can be tuned by the sacrificed layers of PPy. CdS@void@SiO2 YSNs exhibit excellent photostability with a considerably low level of Cd 2+ concentration at <30 ppm, which is dropped down 18 times less than ≈520 ppm of CdS. CdS@void@SiO2 YSNs show good dye removal efficiency up to 99.5%, and commendable hydrogen evolution of 126.8 µmol g −1 h −1 . More interestingly, the transparent and porous SiO2 shell in the YSNs has an impressive shielding to organic carrier. Our versatile YSNs have great potential to translate CdS photocatalyst to industrial‐scale application because of its stability and nondestructivity. Abstract : With the help of transparent and porous SiO2 shell, the obtained versatile CdS@void@SiO2 yolk–porous‐shell nanospheres exhibit simultaneously the protection of CdS from photocorrsion and the impressive shielding of textile carrier during photocatalysis.